Clinical Use of Navigation in Lateral Skull Base Surgery: Results of a Multispecialty National Survey among Skull Base Surgeons in Germany - Jödicke, Andreas; Ottenhausen, Malte; Lenarz, Thomas (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective To analyze the current clinical use of navigation at the lateral skull base among skull base surgeons in Germany.Methods A web-based questionnaire was provided to surgeons being head of the department and member of one of the following scientific societies: German Society of Head and Neck Surgery, Maxillo-Facial Surgery, Neurosurgery, and German Skull Base Society. Replies were recorded anonymously. The questionnaire included the estimated case load per year and percent of surgery performed with navigation (middle and posterior fossa), type of navigation, estimates of intraoperative inaccuracy, and reasons for not using navigation.Results Eighty nine out of 99 replies met requirements for final analysis. Overall, 37% of skull base surgeons use navigation on a regular basis (15% use no navigation). Optical tracking is more frequently used than magnetic tracking (71 vs 19). At the middle fossa, ENT surgeons split into routine users (n = 10/36) and rare users (n = 16/36), the latter stating navigation inaccuracy as a major reason for neglecting navigation. Neurosurgeons use navigation at the middle fossa significantly more often and criticize navigation inaccuracy less. At the posterior fossa, navigation is used less frequently by both ENT and neurosurgeons with similar rates of estimated inaccuracy.Conclusions A moderate use of navigation at the lateral skull base was demonstrated. Insufficient accuracy causes ENT surgeons to frequently omit navigation at the middle fossa (not neurosurgeons) and posterior fossa (also neurosurgeons). Higher intraoperative navigation accuracy is needed to enhance the use of navigation at the lateral skull base.
Keywords: skull base; navigation; middle fossa; posterior fossa; accuracy; survey